Migration nation : animals on the go from coast to coast - O'Sullivan, Joanne (Ranger Rick books., 2015)
An introduction to the migration patterns of nine very different types of animals, from gray whales and sandhill cranes to polar bears and monarch butterflies, discusses their life cycles and how to spot them.